TO HAVE AN INTERPRETER – A RIGHT TO A FAIR TRIAL. EVALUATION OF PERSONAL EVIDENCE OBTAINED BY THE HELP OF AN INTERPRETER - HATI, Csilla (Comparative Legilinguistics, 2016)
Abstract. The author is a trainee lawyer, and a graduating PhD student. Her field of research is the principle of directness in the criminal procedure, with special emphasis on the significance of the spoken language, and the possibility of the distortion of the information that is mediated during interpretation. The author supplements her research with her experience obtained during her time as a defense lawyer in criminal procedures. Her aim is to point out how a confession obtained with the help of an interpreter can lead to a false statement of facts. The right to have a free interpreter belongs to the circle of absolute rights of a fair procedure, the deprivation from which makes a procedure unfair in every case. However, improper interpretation bears risks of a similar proportion, as it can apply new meaning to the confessions. Thus, the forensic and questioning rules of interrogation are different when conducted with an interpreter, provided that the interrogator indeed strives to unveil the truth. This information should be part of the basic knowledge of the members of authority and the defense lawyer as well. However, both the judge and the interpreter must keep it in mind that the parties might intentionally apply such linguistic means which result in the distortion of information.